Effect of annealing environment on dielectric properties of erbium oxide. Issue 16 (15th August 2022) - Asad, Samsaam uddin; Rehman, Sameem Ur; Tariq, Huma; Perveen, Saima; Amin, Faheem; Nadeem, Muhammad; Azad, Fahad
Abstract: Erbium oxide due to its large polarizability and wide bandgap possesses superior dielectric properties and low leakage current. To study the effect of annealing environments on dielectric properties of erbium oxide, it was annealed under argon and air environments. Complex impedance analysis was performed to investigate dielectric properties, relaxation and conduction processes of the annealed samples. The decrease in grain size and increase in surface area, due to annealing in argon environment, resulted in over 2-fold increase in dielectric constant as compared to conventionally used SiO2 (Effendy et al., 2017) [1]. The annealing in reducing environment also happened to widen the bandgap energy of erbium oxide. Annealing of erbium oxide in inert environment was proved to be better for the enhancement of dielectric properties, owing to creation of smaller grains with larger grain boundaries.